Pattern Based Cache Management Policies - Dafre, Namrata; Shrawankar, Urmila; Kapgate, Deepak (International Journal of Computer Sciences and Engineering, 2014)
In a computer architecture Cache memory have been introduced to balance performance and cost of the system. To improve the performance of a cache memory in terms of hit ratio and good response time system needs to employ efficient cache replacement policy. Unified Buffer cache management, Program Counter-based Classification, Detection based Adaptive Replacement, Robust Adaptive buffer Cache management scheme and Block Pattern Based Buffer Cache Management are some of the existing policies. But they have some disadvantages like they were not able to exploit both recency and frequency information, some of them could not exploit all type of reference regularities, some of them have high memory overhead. So we require more advanced policies to improve the performance. In this work we are proposing the block access pattern based replacement policy which predicts future request of a block based on history of response time for respective data block. Block access pattern based replacement policy leads to effective improvement in buffer cache hit ratio and reduced response time.